Dorsal Hand and Foot Mycosis Fungoides: Looking Beyond Mycosis Fungoides Palmaris et Plantaris - Kee Suck Suh; Jang Hwan Jung; Sun Mun Jeong; Min Soo Jang; Jong Bin Park (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)